Haciendo frente a la discriminación y a la exclusión Las experiencias de migrantes chinos libres en las Américas desde una perspectiva transregional y diacrónica - Manke, Albert (Ensayos InterAmericanos, 2020)
This essay takes an inter-American and transpacific look at historical processes of discrimination and exclusion of free Chinese migrants in the Americas from the sixteenth to the twentieth century. The analysis of the correlation between migration, liberalism and racism will allow us to gain a better understanding of the situations of discrimination faced by Asian immigrants and others considered as "non-Whites" in the United States, Europe and other parts of the world. Today, this issue is once again gaining relevance, particularly in light of the xenophobic and anti-Chinese reactions that have arisen with the coronavirus pandemic.